Understanding Profit Accounting Practices by Binthe Biluhuta Sellers - Paputungan, Vindi; Mohamad, Roni; Rahmatia, Rahmatia; Thalib, Mohamad Anwar (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2025)
Purpose: This study aims to understand profit accounting practices by binthe biluhuta sellers based on local cultural values.Method: This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy.Results: The study results show that binthe biluhuta sellers practice value-sharing-based profit accounting, among others. This value is reflected through the use of profits not only to fulfill personal interests but profits from selling binthe biluhuta are also used to help each other. In Gorontalo's Islamic culture, elders often internalize the value of sharing among others through the expression "delo tutumulo lambi." The meaning of this expression is a statement of life that has benefited many people.Implications: The results of this study seek to preserve accounting based on local culture.Novelty: The novelty of this research is that it presents the concept of profit accounting by binthe biluhuta sellers on local cultural values and religiosity.